Synthesis and Antifungal Activities of N3-Substituted Quinazolin-4-one Catalyzed by 3-Methylimidazole Ionic Liquids - Liu, G.; Liu, C.P.; Ji, C.N.; Sun, L.; Liu, X.G.; Wen, Q.W.; Xu, S.G. (Asian Journal of Chemistry, 2013)
N3-Substituted quinazolin-4-one was synthesized by alkyl bromide and quinazolin-4-one was synthesized by anthranilic acid and formamide, catalyzing in various 3-methylimidazole ionic liquids and TBAB. The results showed that the yield of N3-substituted quinazolin-4-one increased appreciably and the reaction time shorted under ionic liquids and TBAB. Using 1-methyl–3-(2-hydroxyl-3-acetoxylpropyl)imidazolium fluoroborate or 1-propyl-3-methylimidazole fluoroborate as catalyst, the yield of N3-benzylquinazolin-4-one reached 85.1 and 82.0 %, increased 27 % more than the yield of traditional conditions. The compounds were evaluated for their in vitro antifungal activity against Fusarium graminearum, Fusarium oxysporum and Cytospora mandshurica. Compound 3f inhibited Fusarium graminearum with EC50 28.85 μg/mL, Fusarium oxysporum with EC50 24.68 μg/mL and Cytospora mandshurica with EC50 37.67 μg/mL.